Do health literacy disparities explain racial disparities in family-centered care for youths with special health care needs?. Issue 4 (April 2021) - Chisolm, Deena J.; Keedy, Hannah E.; Dolce, Millie; Chavez, Laura; Abrams, Mary Ann; Sanders, Lee
Highlights: Youth with special health care needs benefit from family-centered care (FCC). We explored if racial disparities in FCC were associated with health literacy. African-Americans (AA) had significantly lower levels of FCC. Health literacy interventions may not reduce the racial disparity in FCC. Abstract: Objective: To explore the relationship among youth health literacy, parental health literacy, and family-centered care (FCC) for youth with special health care needs (YSHCN) and assess potential racial disparities. Methods: HL and FCC were assessed in 486 Medicaid-enrolled YSHCN (ages 12–18) and their healthcare-responsible parent/caregiver. Analyses assessed racial differences in HL and FCC for parents and youth using logistic regression. Results: Half of youth and over 80 percent of parents had adequate HL (REALM score ≥62). Adequate HL was significantly lower in African Americans (AA) for both YSHCN and parents. Only 57 % of parents and 29 % of YSHCN reported FCC. AA YSHCN reported significantly lower levels of FCC compared to White YSHCN. AA parents trended lower for FCC compared to Whites, though the disparity was not significant. AA youth and parents had significantly lower odds of reporting that doctors spent enough time with them compared to Whites. Conclusion: Results suggest that AA and those with less than adequate health literacy experience lower FCC, however the relationship between race and health literacy does not explain the racial disparity in FCC. Practical Implications: Provider time spent focused on HL may not reduce the racial disparity in FCC, but opportunities for improvement exist.